Host size preferences of vascular epiphytes are reflected in their spatial distributions: a study of a mature broadleaf evergreen forest in Kochi, Japan. Issue 5 (2nd September 2020) - Seto, Mifumi; Higa, Motoki; Ishikawa, Shingo
ABSTRACT: An understanding of epiphyte richness and the factors controlling it is fundamental for conserving the diversity of natural mesic forests. Host tree size is a determinant of epiphyte occurrence; however, previous studies have produced opposing results regarding the spatial distribution (patchy or random) of diversity. This study assessed the relationship between host tree size preference and the distribution of vascular epiphytes in a mature broadleaf evergreen forest in Kochi, southern Japan. The host tree size preferences of epiphytes occurring on more than eight of 247 host trees were assessed using generalized linear mixed models. We established a 0.59-ha forest census plot in a valley bottom with abundant epiphytes, and used Ripley's L function and envelope simulations to assess the spatial distribution patterns for an epiphyte species showing lower size preference, and the large trees to which many epiphyte species were expected to adhere. We found that Davallia mariesii, Loxogramme salicifolia, Bulbophyllum inconspicuum, Dendrobium moniliforme, Eria japonica, and Ribes ambiguum showed higher host size preferences. The large trees to which these epiphytes were expected to adhere were randomly distributed. By contrast, Lemmaphyllum microphyllum and Lepisorus onoei showed lower host size preferences. The spatial distribution of trees with L. microphyllum showed a clustered pattern. These results imply that host size preference may vary among epiphyte species depending on their ecological traits and be reflected in their spatial distributions. Therefore, epiphyte distributions are not necessarily either random or clustered spatially.